Gambaran Minat Terapis Gigi dan Mulut Terhadap Peluang Berwirausaha Di Bidang Media Edukasi Roll Book - Amirullah, Fuad; Laela, Dewi Sodja; Octaviana, Devy; Nurjanah, Neneng (Jurnal Terapi Gigi dan Mulut, 2024)
Dental caries is a dental health problem that damages the hard tissue of the teeth and is a problem that often arises in the community. Tooth decay that is quite a lot in the community is a special concern of dental and oral therapists in emphasizing the number of tooth decay in the community. One way to reduce the high rate of tooth decay in the community is through education using the media. Tooth decay that has quite a lot of impact on the use of educational media. The use of many educational media is a driving factor for the emergence of interest from dental and oral therapists to take advantage of entrepreneurial opportunities found in educational media. The purpose of this study is to determine the interest of dental and oral therapists in entrepreneurial opportunities in the field of roll book educational media in the city of Bandung. The type of research used is descriptive research. The research subject in this design is a Dental and Oral Therapist in Bandung City. Samples in the study were taken using purposive sampling techniques with a total of 80 people. The expected benefit of this study is the known interest of dental and oral therapists in entrepreneurial opportunities in roll book educational media. The results showed that 77.5% of dental and oral therapists had an interest in entrepreneurship and 88.8% considered roll book educational media to have the opportunity to be used as business opportunities in the field of educational media. So it can be concluded that dental and oral therapists have a very high interest in entrepreneurship and roll book educational media have the opportunity to be used as entrepreneurial opportunities by dental and oral therapists.